THE DYNAMICS OF LAND USE CHANGE IN PADANG CITY FOR HYDROLOGICAL MODELING - Yudi Antomi; Ernawati; Triyatno; Ikhwan; Siti Fatimah (GEOMATE Journal, 2019)
The purpose of this study is to predict future land use scenarios from a spatial perspective and quantitatively calculate how hydrological balance in Padang City as part of environmental services. This study uses temporal Landsat images, field surveys, focus group discussions, and analysis of the impacts of land-use change and its solutions. Field surveys were conducted to test the accuracy of field interpretation and data collection such as hydrology and morphology (physiography). The result of this study is the wide difference in land use prediction with the free scenario and the bound scenario is not very significant. The results of the research in the hydrological model show that Padang City has experienced an increase in the surplus of surface water due to changes in land use from natural areas to anthropogenic. Land-use scenarios that represent the use of sustainable environmental services are to revise the existing Padang City spatial pattern through environmental service assessments to obtain sub-catchments or sub-catchments that need to be improved (rezoning) in accordance with the application of zoning patterns.